Adapting Australian coastal regions to climate change: A case study of South East Queensland - Smith, T F; Choy, Darryl Low; Thomsen, D C; Serrao-Neumann, S; Crick, Florence; Sano, M; Richards, R; Harman, Ben; Baum, Scott; Myers, S; Sharma, Vigya; Bussey, M P; et al. (CRC Press, 2015)
Coastal communities are in the front line of climate change. Escalating problems created by sea-level rise, more intense coastal storms, ocean acidification and other repercussions of climate change will exacerbate already pervasive impacts resulting from rapid coastal population growth and development intensification. Coastal communities will only survive and prosper in the coming decades if all concerned make a concerted effort to improve their resilience and adaptability. Telling the stories of real-world communities in diverse coastal settings, this book draws upon the latest research findings from a wide range of disciplines. Case studies are drawn from all around the world and from countries with varying levels of development including America’s Gulf of Mexico coast, Australia, Brazil, Britain, China, New Zealand, The Maldives, South Africa, Bangladesh and Vietnam. [Book Synopsis]